What is the status of soccer injuries among female players? A systematic review - Müller, R. W.; Masenya, T.; Ellapen, T.-J.; Swanepoel, M. (African Journal for Physical, Health Education, Recreation and Dance, 2016)
This review provides an overview of the literature pertaining to female soccer injuries from 2007-2016. The dissemination of female soccer injury surveillances in Africa, America and Europe has been described in regards to their most prevalent anatomical site and injury type. Both intrinsic (quadriceps angle, body mass index (BMI), overuse injuries) and extrinsic risk factors (tackles by opponents, poor landing) associated with soccer injuries were examined. Large BMI and overuse injuries showed significant positive correlations with the incidence of soccer injuries. However, the mechanism of these risk factors` contribution to injuries has not been established. The controversy regarding the association of deviant quadriceps angles and knee injuries has been described. Player position also plays a role as could be seen with midfielders that sustain the most injuries due to their high work rate. Future direction into specific areas of research has been identified to increase the body of evidence concerning the type and mechanism of female soccer injuries.